ANALISIS KUALITAS PELAYANAN PERIJINAN PADA BADAN PELAYANAN PERIJINAN TERPADU (BPPT) KABUPATEN GROBOGAN - Sari, Retno Novita; Dwimawanti, Ida Hayu; Widowati, Nina (Journal of Public Policy and Management Review, 2015)
BPPT (Integrated License Service Cooperative) in Grobogan Regency is one of regional government cooperative in Grobogan, because of that BPPT the society is expected to get a lots of ease in public service, especially in administrative service about the license. Problems of the license service for BPPT are lack of the sufficiency facility and inappropriate time of the license letter publication with the obtain standard. This research and analyzes the license service quality, and dimensions thet support and hamper the service. This research user qualitative descriptive research. This research is based on five dimensions from the theory that is proposed by Zeihaml-Parasuraman-Berry, that are : Tangible, the unsufficiency facility. Reliability, inappropriate time of license letter publication. Responsiveness, perceptive capacity of the officials for applicant complaint. Assurance, friendliness and justice of the afficials. Emphaty, the officials’attention to the applicant. The license service for BPPT in Grobogan Regency is still less satisfy, becauses there is still a deficiency in any dimensions. Suggestion for the dimensions that hamper the license service are : add the unsufficiency facility, make a communication with the afficials.